The role of traditional foods in shaping the social cultural values of Indonesian society - Ida Ayu Junica Larassati; I Nyoman Suka Sanjaya; Nazula Silma; Shamim Ferdous; Debashish Roy; Md. Gulam Mokta Dhir; Mohammad Kamrul Ahsan; Yasotha Nair Tramankuti; Robinson Onuora Ugwoke (Journal of Commerce, Management, and Tourism Studies, 2026)
Traditional foods are deeply embedded in Indonesian society, serving as a cornerstone of social and cultural identity and a vital element of daily life. This study delves into the complex relationship between traditional foods and the social cultural identity of Indonesians, emphasizing the need for their preservation. The objective of this study is to analyzing factors of Traditional Foods that shapes the Social Cultural Identity of Indonesian Society in order to preserved Traditional Foods through a comprehensive document study method, the research explores the definition of General Traditional Foods and Social Cultural Identity, examining the interconnectedness between these two concepts. The study investigates how traditional foods serve as a reflection of social cultural identity, highlighting their diverse values in ceremonies that shaped Indonesian Society. Besides, this paper also contains explanation of social culture threats potential that could happens in this era. By referencing relevant documents and journals, the study aims to provide a robust analysis of the multifaceted relationship between traditional foods and social cultural identity in Indonesia, ultimately contributing to the preservation of this vital cultural heritage.